Isolasi Alginat Rumput Laut Coklat (Sargassum sp.) menggunakan Jalur Kalsium Alginat - Susiana Prasetyo S; Olivia Juliani; Asaf Kleopas Sugih (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
Alginate has been widely used in industrial field because of its natural properties as gelling agent. Brownseaweed, especially Sargassum and Turbinaria as the alginate sources are widely grown in Indonesia; butunfortunately there has yet to be any alginate industry in Indonesia. Alginate content in Sargassum isconsidered quite large, about 35%, whereas alginate content in Turbinaria is only around 20-25%. In thisresearch, sodium alginate was isolated from dried brown seaweed (Sargassum sp.) which first passedthrough the acid treatment using 0,5%-b/v HCl and alkaline treatment using 0,5%-b/v NaOH. Extraction wasdone in batch, using 2%-b/v Na2CO3 solvent. The chosen post-treatment method was through the Ca-alginatepath with experimental design Reponse Surface Methods-Central Composite Design with 5 center point. Thevaried variable was the concentration of CaCl2 (0,11 – 2,09 M) and the ratio of CaCl2 solution/alginateextract (0,48 – 4,02 g/g). The result showed that higher concentration of CaCl2 increased the yield, viscosity,and ash content. As the ratio of CaCl2/alginate extract got higher, the viscosity had the tendency to decreaseand the ash content increased. Yield of the obtained sodium alginate powder was 6,95 -30,7%; 1,48 – 11,85cP viscosity; ash content about 18,46 – 52,65%; and water content around 6,14 – 8,32%. The optimumcondition was obtained at CaCl2 concentration of 1,02 M and the ratio of CaCl2/alginate extract about 2,01g/g with 27,72% yield, 11,38 cP viscosity, 19,56% ash content, and 6,14-8,32% water content of sodiumalginate.